We remember the land: Quebec geography and the question of Indigenous memory - Desbiens, Caroline; RIVARD, Étienne; Hirt, Irène (Cahiers de géographie du Québec, 2017)
International audience In Quebec, many collective territorial identities coexist, but they do not all have the same visibility. In 2006, Étienne Rivard spoke of a ‘’geography of absence’’ regarding questions of Indigenous territorial identity. Starting from this premise, we explore the unevenness between the importance of Indigenous issues in current affairs and the contribution of geographers in shedding light on these issues. If Quebec academic geography often glosses over the diversity of territorialities in the province, Inuit and First Nations, on the other hand, continue to trace the outlines of what an understanding of Quebec that fully integrates the Indigenous components of its territory could be. Using two examples – one relating to place names and the other to an Indigenous cultural festival – we discuss the growing visibility of Indigenous peoples in Quebec space, in Northern as well as urban regions. En Quebec coexisten varias identidades colectivas vinculadas al territorio, pero no todas son igualmente perceptibles. Etienne Rivard calificó de “geografía de la ausencia” la manera de tratar el tema indígena. A partir de esa aserción, estudiamos la disparidad actual entre la importancia del tema indígena y el aporte de los geógrafos para entender la problemática. Si la geografía universitaria quebequense borra a veces la diversidad territorial quebequense, en cambio, los Inuit y las Primeras Naciones no paran de delinear lo que podría ayudar a comprender un Quebec que integre completamente los componentes indígenas del territorio. A partir de dos ejemplos – uno sobre la toponimia y el otro sobre una fiesta cultural – analizamos la visibilidad creciente de los pueblos indígenas en el espacio quebequense, tanto en las regiones nórdicas que en el medio urbano Au Québec, plusieurs identités collectives liées au territoire coexistent, mais elles n’ont pas toutes la même visibilité. En 2006, Étienne Rivard avait parlé d’une « géographie de l’absence » en ce qui a trait à la question autochtone. ...